Academic Guidance Management in Islamic State University Sunan Gunung Djati Bandung - Nani Nuranisah Djamal; Medina Chodijah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2019)
This research starts from the observations of researchers regarding the condition of the academic guidance at UIN Sunan Gunung Djati Bandung. Academic advisers are lecturers who are appointed and assigned the task of guiding a group of students who aim to help develop the individual potential of students. However, the results of the observation illustrate that the role has not yet proceeded as it should and not accompanied by clear and detailed guidelines for both the lecturer and the students themselves.This study aims to obtain an ideal academic guidance management model design for students at UIN Sunan gunung Djati Bandung by considering: a) general description of academic guidance experienced by students; b). operational student academic guidance; and c). Academic guidance content provided to students.In this study there is only one variable, namely academic guidance management which means the application of management functions in academic guidance activities. The approach used in this research is mixed methods research, where the researcher seeks and analyzes the data obtained both quantitatively and qualitatively simultaneously, which is then processed and presented using descriptive statistics. The respondents in this study were students and lecturers who were representatives of 8 faculties at UIN Sunan Gunung Djati Bandung.The results of the study are presented in 4 major sections, namely; general description of academic guidance, operational academic guidance, academic guidance content and academic guidance management that have been taking place at UIN Sunan Gunung Djati Bandung. General description of academic guidance contains the objectives of academic guidance, rights, and obligations of academic supervisors and guidance students. The operational academic guidance of students is focused on the point of time guidance, guidance cards and indicators of the success of guidance. In the aspect of academic guidance content given to students, researchers focus on 4 points, namely; academic guidance, personal guidance, social guidance, and career guidance. Management in academic guidance activities themselves have several functions that have not been discussed in detail in this study. This is because researchers only focus this research on the functions of planning, organizing and controlling. The function of decision making, staffing, communication and direction is highlighted by the researcher on the proposal or recommendation of the ideal academic guidance management pattern that should apply in UIN Sunan Gunung Djati Bandung.Based on the data obtained then the researcher gives advice; both theoretical, suggestions for further research and suggestions for validating the design of academic guidance management that is ideal for UIN Sunan Gunung Djati Bandung which has been designed by researchers.